2021
DOI: 10.1089/end.2020.0549
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve for Robotic-Assisted Laparoscopic Retroperitoneal Lymph Node Dissection

Abstract: Introduction: Robotic retroperitoneal lymph node dissection (R-RPLND) is a challenging procedure. We hypothesized that surgical times and operative complications would decrease as surgeons became more facile with R-RPLND. Materials and Methods: We retrospectively reviewed 121 consecutive R-RPLNDs performed at Naval Medical Center San Diego and Mayo Clinic Arizona by 4 fellowship trained robotic surgeons between 2008 and 2018. Linear regression was used to analyze independent predictors of setup time, operative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Studies performing laparoscopic and robotic assisted surgeries report satisfactory therapeutic results and low to no morbidity. [158][159][160][161][162] However, a study assessing patients referred to Indiana University for recurrence reported aberrant recurrence patterns after minimally invasive surgeries. All five patients had recurrences in abnormal locations compared with past routine experience.…”
Section: Salvage Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies performing laparoscopic and robotic assisted surgeries report satisfactory therapeutic results and low to no morbidity. [158][159][160][161][162] However, a study assessing patients referred to Indiana University for recurrence reported aberrant recurrence patterns after minimally invasive surgeries. All five patients had recurrences in abnormal locations compared with past routine experience.…”
Section: Salvage Treatmentmentioning
confidence: 99%
“…In recent years there have been initiatives to decrease the morbidity of surgery with minimally invasive surgery. Studies performing laparoscopic and robotic assisted surgeries report satisfactory therapeutic results and low to no morbidity 158159160161162. However, a study assessing patients referred to Indiana University for recurrence reported aberrant recurrence patterns after minimally invasive surgeries.…”
Section: Management Of Gctsmentioning
confidence: 99%
“…(3) When tumors are large, selection bias of surgical methods may affect the results ( 73 ). MIS probably brings some surgical difficulties to surgeons ( 21 , 22 , 66 , 70 , 74 ), reducing the surgical effect. (4) Pneumoperitoneum environment may be a prognostic factor in patients undergoing MIS.…”
Section: Discussionmentioning
confidence: 99%
“…R-RPLND is technically challenging with a significant learning curve, even when performed at high-volume centers. This is demonstrated by continuously decreasing operative times and improved outcomes across 121 cases [40]. Thus, surgical experience and operative technique may contribute to variation in peri-operative outcomes across studies.…”
Section: Complications and Limitationsmentioning
confidence: 99%